Heavy metal resistance mechanisms in actinobacteria for survival in AMD contaminated soils - Schmidt, Andre (2005)
A site in the former uranium mining area of Eastern Thuringia near Ronneburg was investigated with regard to effects of acid mine drainage (AMD) on reactive transport and bioattenuation. Processes involved in this attenuation might include physico-chemical reactions in reactive transport as well as activities of microorganisms for bioattenuation. In order to test the influence of the soil microbes, a mapping was carried out including both hydrogeochemical and microbiological parameters. Mapping of contamination was performed along the banks of a creek in a 900 m stretch in 50 m steps by hydrogeochemical analysis of water extracts of soil samples, while general microbial activity was scored by examining soil respiration. The soil samples with high heavy metal load did show low soil respiration as a parameter for microbial activity and plating revealed minimal counts for spore producing bacteria at these contaminated locations. Actinobacteria strains isolated from adjacent locations revealed high levels of resistance as well as high numbers of resistant strains. Specific responses in actinobacteria were investigated after isolation from each of the 18 measuring points along the creek. Specific adaptation strategies and high yields of (intra)cellular heavy metal retention could be seen. Several strategies for coping with the high heavy metal contents are further discussed and genes for proteins expressed specifically under high nickel concentration were identified by two-dimensional gel electrophoresis. © 2005 Elsevier GmbH. All rights reserved.